Development of Highly Selective Support for CO Hydrogenation to Light Olefins with Partially Passivated Iron Catalysts. Issue 14 (27th May 2019) - Xing, Yu; Jia, Gaopeng; Liu, Zhenxin; Fang, Shaoming; Zhao, Chenxi; Guo, Xuehui; Suib, Steven L.
Abstract: To rule out disturbances from water‐soluble efficient promoters (e. g., K2 O or combination of S/Na), a simplified iron/support catalyst system was employed to investigate novel supports for the catalytic conversion of syngas (CO+H2 ) to light olefins (FTO). A series of supports with nominal compositions of ZnAl2 O4 ⋅ x Al2 O3 ( x =1, 2, 3) were prepared by coprecipitation and subsequent high temperature calcination at 1200 °C for 24 h to generate partially passivated ZnAl2 O4 and Al2 O3 phases, through which each formed component of a catalyst may minimize interactions among them and exhibit unique activity. Iron catalysts were prepared by incipient wetness of iron salts over these supports. At a total pressure of ca. 20 bar and a CO conversion of 35 %, a catalyst with a nominal composition of 15 %Fe/85 %(ZnAl2 O4 ⋅ 3Al2 O3 ) exhibits a surprising C2 = ‐C4 = hydrocarbon distribution of 58 %, which reaches a huge increase by almost 100 % in comparison with iron catalysts over regular supports (e. g., carbon, gamma‐Al2 O3, etc.). This catalyst demonstrates the 1200 °C passivated ZnAl2 O4 ⋅ 3Al2 O3 as probably the most selective support material for iron‐based FTO catalysts. At CO conversion of 35 %, the contents of ethylene in C2, propylene in C3, and butylene in C4 products achieve extraordinary values of 82 %, 92 %, and 91 %, respectively. Abstract : Solid, solid as a rock ! A 1200 °C passivated solid base composite, ZnAl2 O4 ⋅ 3Al2 O3, was demonstrated to be probably the most selective support material for iron‐based Fischer‐Tropsch to light olefins (FTO) catalysts, of which the C2 = ‐C4 = hydrocarbon distribution increased by almost 100 % in comparison with Fe catalysts on regular supports